Land use change in coastal zones of China from 1985 to 2020 - Zhang, Xiongyi; Ning, Jia (Frontiers in Marine Science, 2024)
Coastal regions stand as pivotal zones of interaction between the marine and terrestrial environments, holding substantial significance for both ecosystems and human societies. Since the 1980s, China’s coastal zones (CCZ) have undergone rapid economic expansion, a surge in urban development activities, and a considerable population increase, instigating significant alterations in land use along the coast. However, in recent years, studies regarding changes in land use along China’s coastal zones have been notably scarce. Utilizing the Comprehensive Lands Cover Database (CLCD) dataset, this study scrutinized the spatiotemporal patterns of land use along the Chinese coastline since 1985. It delved into the temporal and spatial variations in land use, ecological land transformations, and the spatiotemporal evolution of land use development intensity, examining these facets across provinces, municipalities, and different distance bands from the coastal zone. The research findings indicated: Overall, cropland and forest land predominantly occupied coastal zones, encompassing over 80% of the total area. Between 1985 and 2020, the primary changes involved a decrease in cropland and an increase in construction land, with a reduction of 5.97% in cropland, largely transitioning into construction land (84927.21 km2) and forest land (4218.55 km2), resulting in a 5.98% increase in construction land. Despite the intensification of land development, ecological land exhibited an initial rise followed by a declining trend. There existed distinct disparities in land use patterns among provinces and cities, with cropland and forest land prevailing in all areas except Macau. Construction land and land use development intensity witnessed significant increases, most notably in Macau and least pronouncedly in Guangxi. Variations in ecological land alterations were considerable, with Hebei and Guangdong witnessing increases while other regions tended towards stability or reduction. Each distance band manifests a unique land use pattern. Except for the 100-150 km zone, construction land demonstrates an increasing trend across all bands. Ecological land expanded initially but fluctuated further from the coastline. Land use development intensity decreased initially, then stabilized, with the 0-10 km zone showed the highest development intensity. Analyzing the spatiotemporal changes in land use along China’s coastal zones from 1985 to 2020 can offer valuable insights into the management and sustainable development of China’s coastal zones.